Isolation, characterization, and genomic analysis of a lytic bacteriophage, PQ43W, with the potential of controlling bacterial wilt - Huang, Binbin; Ge, Long; Xiang, Dong; Tan, Ge; Liu, Lijia; Yang, Lei; Jing, Yongfeng; Liu, Qingshu; Chen, Wu; Li, Ye; He, Haoxin; Sun, Huzhi; et al. (Frontiers in Microbiology, 2024)
Bacterial wilt (BW) is a devastating plant disease caused by the soil-borne bacterium Ralstonia solanacearum species complex (Rssc). Numerous efforts have been exerted for control BW, effective, economical and environmentally friendly approaches are still not available. Bacteriophages is a promising resources for control the bacterial diseases that including of BW. So, in this study, a crop BW pathogen of lytic bacteriophage was isolated and named PQ43W. Biological characterization revealed PQ43W had a short latent period 15min, 74 PFU/cell of brust sizes and well stability at wide range temperatures and pH, but a weak resistance against UV radiation. Sequencing revealed phage PQ43W contained a circular double-stranded DNA genome of 47,156 bp with 65 predicted open reading frames (ORFs), genome annotation showed well environmental security for the PQ43W that no tRNA, antibiotic resistance, virulence genes was contained. Taxonomic classification showed PQ43W belongs to a novel genus of subfamily Kantovirinae under Caudoviricetes. Subsequently, a dose of PQ43W for the phage therapy in controlling crop BW was determined that 10 8 PFU*20ml per plants with non-invasively irrigation root application twice by pot experiment. Finally, a field experiment of PQ43W showed a better control effect in controlling crop BW to compare with the conventional bactericide Zhongshengmycin, significantly. Therefore, bacteriophage PQ43W is an effective bio-control resource for controlling BW diseases, especially for the crop cultivation.